A pragmatic study of mid‐mixture insulin and basal insulin treatment in patients with type 2 diabetes uncontrolled with oral antihyperglycaemic medications: A lesson from real‐world experience. Issue 8 (11th May 2020) - Zhang, Xiaomei; Ma, Yujin; Chen, Hong; Lou, Ying; Ji, Linong; Chen, Lulu
Abstract: Background: Chinese guidelines for the treatment of type 2 diabetes (T2D) recommend basal or premixed insulins as insulin starters after failed oral antihyperglycaemic medication (OAM). This pragmatic study compared effectiveness and safety of add‐on basal insulin analog (BI) and mid‐mixture insulin analog (MMI; 50:50 premixed insulin) as starter insulin regimens in Chinese patients with T2D in a real‐world setting. Materials and Methods: This was a multicentre, open‐label, randomized, parallel, pragmatic trial. Patients receiving OAMs were randomized 1:1 to BI (n = 410) or MMI (n = 404) for 24 weeks. Insulin titration and OAM adjustment were determined by investigators following usual standard‐of‐care. The primary outcome was change in glycated haemoglobin (HbA1c) from baseline. Results: Least‐squares mean changes in HbA1c from baseline to week 24 were −2.00% and −2.15% for BI and MMI groups, respectively ( P = .13). The MMI group demonstrated a greater reduction in concomitant OAM therapies used than BI group (53.8% vs. 35.3%, respectively; P < .001). Very limited daily insulin dose increments were observed from baseline to week 24 in both BI and MMI groups (2.5 U/day and 1.8 U/day, respectively). Although both insulin analogs were well‐tolerated without severe hypoglycaemia, small weight gains were seen with both treatments. Higher total hypoglycaemia rates were noticed with the MMI group, while nocturnal hypoglycaemia events were comparable. Conclusions: In real‐world settings, BI and MMI provided similar improvement in glucose control without conceding hypoglycaemia. The BI group received a greater number of OAMs in real‐world settings. Limited insulin dose titration was observed, while more adjustments occurred with OAM usage.